EVALUATION OF THE ACHIEVEMENT SPORTS POLICY OF WEST JAVA PROVINCE - Firdaus, Fauzi Setiadi (Universitas Pendidikan Indonesia, 2023)
The development of sports for achievement requires adequate policy support. Various challenges faced in realizing achievement sports, both structural and infrastructural obstacles, can solve the problem of achievement achievement. This condition is related to achievements that are still weak. The purpose of the study was to evaluate the achievement sports policy of the province of West Java. The analysis method uses descriptive qualitative with interactive data analysis. The results showed that the success of the policy lies in communication, interorganizational coordination and commitment as well as the behavior of agents in the field. The effectiveness, equity, responsiveness and accuracy of agents in implementing policies are still very lacking. Theapplication applied in the Futsal sports branch, especially in the West Java area, is still weak. Wadah or clubs that nurture the potential of athletes well, because the policies made are not ready to be used in the field. good cooperation between athletes and elements of the government is still lacking. The conclusion that the policy to realize achievements in the sport of futsal has not been effective in encouraging futsal achievements. Theoretical implications: the need for a thorough policy evaluation of futsal sports achievements in terms of interactions between organizations, as well as agents in the field. Practical implications: The success of the policy lies in the coordination, communication and commitment of the government in realizing the sport of achievement.